SMART TOURISM TECHNOLOGY AS A DRIVER OF SUSTAINABLE RELIGIOUS TOURISM AND VISITOR LOYALTY: EVIDENCE FROM PAKISTAN (Contemporary Journal of Social Science Review, 2025)
This study examines how smart tourism technology (STT) can enhance the sustainability of religious tourism destinations and foster visitor loyalty in Pakistan. Drawing on the Technology Acceptance Model (TAM) and related theories, we develop a conceptual framework in which key attributes of STT (informative, accessibility, interactivity, personalization, security) influence tourists’ technology adoption, perceived enjoyment, sustainable tourism behavior, and revisit intentions. A quantitative survey of 499 visitors at major religious heritage sites in Pakistan was conducted, and the proposed relationships were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that all five STT attributes significantly contribute to positive technology-supported tourist experiences, which in turn lead to higher technology adoption and perceived enjoyment. STT usage shows a direct positive effect on both sustainable tourism practices (β≈0.24, p